The historical fate of the rural settlement network in Russia: The case of Tomsk Oblast, 1940s-1980s - Shevtsov, Vyacheslav V. (Social history)
This article discusses the practice of designing and restructuring the rural settlement network of Tomsk Oblast from the 1940s through to the 1980s. The focus is on those rural settlements that were seen as having no prospect of further economic development, and whose consolidation constituted the basis of the USSR resettlement policy. Planning schemes and area planning projects created for some areas of Tomsk Oblast are examined, and the results of the implementation of these projects are summarized. The article also explores the socio-economic development of Tomsk villages and the agricultural production crisis in the north of Tomsk Oblast with regard to their impact on migration in the region's rural areas and subsequent depopulation thereof. It identifies the influence of the state reforms on the relationship between the Soviet village and the Soviet authorities, and changes in the adaptation practices of the Soviet peasants in response to the state's policy to increase labour productivity on collective farms.